491 Evaluating the long-term impact of a practice-oriented research training program for clinical and translational research staff. (April 2022) - Samuels, Elias M.; Champagne, Ellen; Murphy, Susan; Kalpakjian, Claire
Abstract : OBJECTIVES/GOALS: The objective of this evaluation is to evaluate the long-term impact of the PORT program on the clinical and translational research careers of the participating research staff. The impact of the program is best demonstrated through measures of the scientific contributions of the participants as well as their professional advancement over time. METHODS/STUDY POPULATION: The PORT program participants were tracked through the collection of instructional and public records, including the collection of their subsequent grant and publications. The clinical and translational research careers of the participants was also assessed, using a measure adapted from the operational guidelines for NCATS' Research Careers Common Metric. A survey was administered to part participants and interviews conducted with participants from the past cohorts. RESULTS/ANTICIPATED RESULTS: The evaluation results demonstrate the PORT program participants made substantial contributions to the advancement of clinical and translational research, particularly through their publication of hundreds of scientific works. In addition, the evaluation results reveal that the program had short-, intermediate- and long-term impact on their research careers, thereby contributing to the advancement of the health research workforce at the University of Michigan for well over a decade. Specific participant cases highlight how individuals utilized their experience and training to advance research agendas and their long-term careers at the institution. These findings can inform the development, implementation and evaluation of similar programs throughout the CTSA consortium and beyond. DISCUSSION/SIGNIFICANCE: Most evaluations of research training and award programs for clinical and translational research staff do not evaluate the long-term impact of CTSA support on the research careers of the participants. The findings of this evaluation can help inform the development of new and more effective workforce development initiatives with long-term impact.